The role of sharia microfinance in micro business development - Fathurrahman, Ayif; Mutmainah, Choironi (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to determine how the differences in sales turnover, the number of workers, the number of goods sold, and the number of customers before and after receiving financing at BMT Artha Amanah Sanden. This research is a type of quantitative descriptive research. The subjects in the study were micro-entrepreneurs who received the financing at BMT Artha Amanah Sanden. Regarding the fundamental issues in microbusiness which are capital and connections, this research is important to show the real form of establishing an effective and mutually reinforcing Islamic economic ecosystem. In this study, a sample of 50 micro-entrepreneurs were selected by the survey method. The data collection techniques in this study used questionnaires and interviews. The analytical tool used was non-parametric analysis method of the Wilcoxon Sign Rank Test. Based on the results of the analysis, it is found that: (1) There is a difference between sales turnover before and after financing from BMT Artha Amanah KC Sanden. (2) There is a difference between the number of workers before and after financing from BMT Artha Amanah KC Sanden. (3) There is a difference between the number of goods sold before and after financing from BMT Artha Amanah KC Sanden. (4) There is a difference between the number of customers before and after financing from BMT Artha Amanah KC Sanden.